Follicular Development Dynamics and Plasma Progesterone Profile during the Estrous Cycle of Dairy Cows - Putro, PP; Wasito, R; Wuryastuty, H; Indarjulianto, S (ANIMAL PRODUCTION, 2008)
A total of five local Friesian cows, 4 to 5 years, healthy, reproductively sound, were used in the study to understand the development dynamics of dominant follicles and plasma progesterone profile during estrous cycle.   Transrectal ultrasonographic examination using real time, B-mode, with 7.5 MHz transducer was performed daily for one full cycle to follow the development of dominant follicle and corpus luteum dynamics.   Blood plasma was collected daily to determine progesterone levels using EIA technique.   Follicular development dynamics and plasma progesterone levels were analyzed statistically using analyses of variance, while correlation between plasma progesterone levels and corpus luteum size were tested using correlation analyses.   The length of estrous cycle in local Friesian cow was 21.00 + 1.00 days.   Follicular dynamics during estrous cycle indicated only had two waves of dominant follicular development.   The first wave of dominant follicle was firstly identified on day 3, reached maximum diameter (11.17 + 0.90 mm) on day 11 and identifiable until day 15.   The second dominant follicle appeared on day 11, reached maximum size on day 21 (13.17 + 0.69 mm) and underwent ovulation on the next day.   The increased diameter of dominant follicle from days 17 to 21 was linear with growth rate of 1.20 + 0.18 mm/day.   Ovulatory dominant follicle had larger size than non-ovulatory ones (P<0.05).   Corpus luteum was ultrasonically detectable from days 5 to 19 of the estrous cycle.   The maximum size of corpus luteum (11.83 + 0.75 mm) attained on day 11, and then regressed substantially till day 19.  Plasma progesterone level started to rise during the luteal phase, reached the peak level on day 12 (4.64 + 0.23 ng/ml) and then decreased steadily till the lowest level (0.42 + 0.05 ng/ml) at the time of estrus.  The plasma progesterone profile and the corpus luteum development were concomitant each other during estrous cycle of the cow.  It can be concluded that the follicular dynamics during estrous cycle in local Friesian cows only had two waves of dominant follicular development, while plasma progesterone levels manifested corpus luteum function throughout the estrous cycle. (Animal Production 10(2): 73-77 (2008) Key Words:  Follicle, corpus luteum, progesterone, estrous cycle, cow